Schwarze Weiblich*keiten: Intersektionale Perspektiven auf Bildungs- und Subjektivierungsprozesse - Bergold-Caldwell, Denise (transcript, 2020)
Experiences of intersectional difference and potentials of racism-critical, postcolonial and Black feminist education brought together in one volume.